Implications of Spinopelvic Alignment for the Spine Surgeon. (20th September 2011) - Mehta, Vivek A.; Amin, Anubhav; Omeis, Ibrahim; Gokaslan, Ziya L.; Gottfried, Oren N.
Abstract: The relation of the pelvis to the spine has previously been overlooked as a contributor to sagittal balance. However, it is now recognized that spinopelvic alignment is important to maintain an energy-efficient posture in normal and disease states. The pelvis is characterized by an important anatomic landmark, the pelvic incidence (PI). The PI does not change after adolescence, and it directly influences pelvic alignment, including the parameters of pelvic tilt (PT) and sacral slope (SS) (PI = PT 1 SS), overall sagittal spinal balance, and lumbar lordosis. In the setting of an elevated PI, the spineadapts with increased lumbar lordosis. To prevent or limit sagittal imbalance, the spine may also compensate with increased PT or pelvic retroversion to attempt to maintain anupright posture. Abnormal spinopelvic parameters contribute to multiple spinal conditions including isthmic spondylolysis, degenerative spondylolisthesis, deformity, and impact outcome after spinal fusion. Sagittal balance, pelvic incidence, and all spinopelvic parameters are easily and reliably measured on standing, full-spine (lateral) radiographs, and it is essential to accurately assess and measure these sagittal values to understand their potential role in the disease process, and to promote spinopelvic balance at surgery. In this article, we provide a comprehensive review of the literature regarding the implications of abnormal spinopelvic parameters and discuss surgical strategies for correction of sagittal balance. Additionally, the authors rate and critique the quality of the literature cited in a systematic review approach to give the reader an estimate of the veracity of the conclusions reached from these reports.